Assessing the sustainability of anticoagulant-based rodent control for wildlife conservation in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Conservation Biology at Massey University, Palmerston North, New Zealand - Sran, Suman Preet Kaur (Massey University, 2019)
Brodifacoum is used extensively to control invasive rodent pest populations in New Zealand. However, there are major concerns regarding non-target poisoning due to brodifacoum, its high persistence and risk of emergence of resistance in targeted rodents. In the present study, I assessed brodifacoum resistance in ship rats and house mice using blood-clotting response (BCR) tests. Mature ship rats of both sexes were live trapped from Akatarawa forest, an area of no known anticoagulant use history in Wellington. A ranging study was performed whereby healthy ship rats were administered increasing doses of brodifacoum to calculate the effective dose, which in ship rats is considered to be the dose giving a 3.6-fold increase in blood-clotting time (this proportional increase is referred to as the International Normalised Ratio, or INR). An unexpectedly high effective dose of 2.9 and 3.8 mg/kg was calculated for male and female ship rats respectively. The calculated effective dose was used to access brodifacoum susceptibility in ship rats captured from nine areas of known brodifacoum use history in the Wellington region and Palmerston North. A total of 54 ship rats were successfully tested, and there was a significant decrease in INR with increasing number of years of brodifacoum use in an area. Despite this evidence of anticoagulant resistance revealed by BCR tests, no mutations conferring anticoagulant resistance were found in VKORC1 gene sequences in tested ship rats. This suggests that resistance may be caused by other pathways. Similarly, BCR tests were performed in house mice using the effective dose from published literature, i.e. 0.52 mg/kg for males and 0.46 mg/kg for females. Twenty out of 26 house mice assessed were found to be resistant to administered dose of brodifacoum, meaning the INR was >5. However, no relationship was observed between the INR value and the number of years of brodifacoum use in an area. Seven of the tested mice were found to have a non-synonymous mutation, Tyr139Cys in exon 3 of the VKORC1 gene. The house mouse individuals carrying this mutation are known to be fully resistance to all first-generation anticoagulants and a second-generation anticoagulant, bromadiolone, but only minor resistance is known to occur towards more potent second-generation anticoagulants. At present, only technical resistance to brodifacoum has been reported in ship rats and house mice, and brodifacoum may still be used effectively to control these rodent populations. However, continual use of brodifacoum may encourage further resistance. Effective long-term control of anticoagulant-resistant populations can only be achieved by use of alternative non- anticoagulant rodenticides.
Figures 1.4, 1.5 & 1.6 were removed for copyright reasons, but may be accessed via their respective sources: Schulman & Furie, 2015 Fig 1; Ishizuka et al., 2007 Fig 1; & Ishizuka et al., 2008 Fig 3.
Keywords: Brodifacoum; Physiological effect; New Zealand; Rodenticides; Pesticide resistance; Blood coagulation tests; Rats; Mice; Effect of pesticides on; 410202 Biosecurity science and invasive species ecology